Korelasi Permainan Tradisional Gobak Sodor dengan Tingkat Kesegaran Jasmani Siswa Putra Kelas IV SD Negeri Cibodas 1 Kota Tangerang (Universitas Negeri Semarang, 2022)
The background research on traditional games are games that have elements of physical activity such as increasing the physical freshness of children. The purpose of this study is whether there is an influence of The Traditional Game of Gobak Sodor on Improving Physical Freshness in the Learning of Male Students in Grade IV SDN Cibodas 1 Tangerang City. This type of research is One Group Pretest-Posttest Design with a quantitative research approach. The population in this study was grade IV male students which amounted to 48 students, all populations were used as research samples so it was called a total sampling study. Data analysis techniques in this study used inferential statistical analysis, hypothesis testing. The results showed that: (1) there was an influence of the traditional game gobak sodor on increasing physical freshness in the learning of grade IV male students of SDN Cibodas 1 TANGERANG CITY with a t value calculate 3.472 > t table 2.011in the level (0.05%) so that Ha is accepted and (2) The percentage by 11% so that the influence of the traditional game gobak sodor on increasing physical freshness. The conclusions of this study are (1) There is an influence of traditional gobak sodor games on increasing physical freshness in the learning of grade IV male students at SDN Cibodas 1 Tangerang City (2) Besar the influence of gobak sodor games on increasing physical freshness in the learning of grade IV male students at SDN Cibodas 1 TANGERANG CITY with an increase percentage of 11%.